Circadian Clock Genes Modulate Immune, Cell Cycle and Apoptosis in the Diagnosis and Prognosis of Pan-Renal Cell Carcinoma - Liu, Shuwen; Cheng, Yongxian; Wang, Shaoxiang; Liu, Huiyu (Frontiers in Molecular Biosciences, 2021)
Background: Pan-renal cell carcinoma (pan-RCC) is mainly divided into renal clear cell carcinoma (KIRC), renal papillary cell carcinoma (KIRP), and chromophobe cell carcinoma (KICH). Pan-RCC is a common malignant neoplasm with a high incidence and poor prognosis. Several studies have demonstrated a close association between cancer development and circadian rhythms; however, the clinical significance and molecular mechanism of the clock gene remain unclear in pan-RCC. Methods: In this study, we systematically characterized the alterations of 15 well-known clock genes of three types of kidney cancer. Bioinformatics methods, including differential expression analysis, survival analysis, signing pathway analysis, co-expression network analysis, and drug sensitivity analysis were used to study the diagnosis, prognostic role, and mechanism of clock genes. Results: Thirteen rhythmic genes fluctuated in circadian rhythm in the kidney tissue of mice, and the opposite trend of these rhythm phases was also found in baboons. There are twelve clock genes that were differentially expressed in at least two types of RCC, of which NR1D1, DBP, BHLHE40, CRY1, and CLOCK had the same trend in RCC. Changes in clock control genes may be regulated through methylation, copy number, and mutations. Five rhythmic genes, including PER2, DBP, PER3, CRY2, and RORA, have significant prognostic role in patient survival in at least two types of kidney cancer. Immune infiltration analysis showed that the expression of these rhythmic genes related to prognosis was positively correlated with the infiltration levels of CD4 and CD8 T cells. Pathway analysis suggests that the clock genes is widely related to cancer-related signaling pathways, such as apoptosis, cell cycle, and other pathways. The PPI network showed that circadian genes are closely linked to cancer-related genes such as HIF-1A, TP53, and ERBB2. Moreover, clock gene expression is correlated with the sensitivity of anticancer drugs such as bleomycin and methotrexate in pan-RCC. Conclusion: Taken together, the abnormal expression of biological clock genes plays an important role in the clinical prognosis of RCC through immunity, cell cycle, and apoptosis. These findings provide a reliable basis for the diagnosis, prognosis, and drug guidance for RCC.